2022
DOI: 10.1002/eat.23708
|View full text |Cite
|
Sign up to set email alerts
|

Appearance and performance‐enhancing drugs and supplements, eating disorders, and muscle dysmorphia among gender minority people

Abstract: Objective: Appearance and performance-enhancing drugs and supplements (APEDS) can be used to enhance muscle growth, athletic performance, and physical appearance.The aim of this study was to examine the lifetime use of APEDS and associations with eating disorder and muscle dysmorphia symptoms among gender minority people.Method: Participants were 1653 gender minority individuals (1120 gender-expansive [defined as a broad range of gender identities that are generally situated outside of the woman-man gender bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…Among college and university males in the United States, 0.2% reported abuse of androgens [6], whereas other estimates in young adults have been 2.2% to 2.8% [7,8]. Among cisgender gay men in the United States, prevalence of androgen abuse was 2.9% [9], whereas lifetime prevalence of androgen abuse was 1.7% among transgender men, 1.1% among transgender women, and 0.7% among gender-expansive (e.g., nonbinary) people [10]. Among competitive and noncompetitive male bodybuilders in Iran, 34% and 27% of participants reported androgen abuse, respectively [11 & ].…”
Section: Introductionmentioning
confidence: 92%
“…Among college and university males in the United States, 0.2% reported abuse of androgens [6], whereas other estimates in young adults have been 2.2% to 2.8% [7,8]. Among cisgender gay men in the United States, prevalence of androgen abuse was 2.9% [9], whereas lifetime prevalence of androgen abuse was 1.7% among transgender men, 1.1% among transgender women, and 0.7% among gender-expansive (e.g., nonbinary) people [10]. Among competitive and noncompetitive male bodybuilders in Iran, 34% and 27% of participants reported androgen abuse, respectively [11 & ].…”
Section: Introductionmentioning
confidence: 92%
“…Recent literature has studied the correlation between exercise abuse, MD, appearance anxiety, and compulsive behavior [ 36 , 40 ]. Findings have suggested a high risk of exercise abuse and body image disorders in recreational exercisers that used fitness products under no supervision [ 36 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Moreover, they have informed that changes in habits, such as radical diets and the use of SS, have been reported as risk factors of MD, exercise abuse, and addictive behaviors in exercisers [ 34 , 35 , 36 , 38 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings have suggested a high risk of exercise abuse and body image disorders in recreational exercisers that used fitness products under no supervision [ 36 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Moreover, they have informed that changes in habits, such as radical diets and the use of SS, have been reported as risk factors of MD, exercise abuse, and addictive behaviors in exercisers [ 34 , 35 , 36 , 38 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Therefore, authors have reported users of SS with high levels of SM, MD and exercise abuse which are vulnerable to a risky intake that may lead to physical and mental problems [ 36 , 37 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations